Tas Kanvas Lukis dengan Perca Endek Bali dan Kain Motif Khas Lombok yang Bernilai Seni dan Ekonomis - Komalayakti, Diah; Mustika, I Ketut; Kondra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
The process of creating something so that it can have added value in the economy is the notion of entrepreneurship. In that case, the creation of a product with innovation and creativity is very important. The use of textile materials in the form of canvas, endek patchwork and typical Lombok fabrics into a product in the form of a painted bag is an innovation in the creative industry and develops creativity. In addition, efforts to preserve the existence of traditional fabrics such as Endek fabrics and typical Lombok fabrics in the midst of modern times that lead to modern culture as a fashion trend can be carried out by collaborating with current trends. Endek is a traditional Balinese cloth that has a variety of motifs. Many endek fabrics are also designed to be clothing, so there is a lot of patchwork left. Meanwhile, typical Lombok fabrics are generally only used for certain activities as traditional clothing, but with creativity the two types of traditional fabrics can become unique works in the form of painted bags in collaboration with canvas as the main material. Bags are a fashion item that cannot be separated from the daily lifestyle of teenagers. The creation of bag products is carried out on a self-manufactured basis. So, of course it has high artistic value. The chosen bag design is a consideration of the uniqueness and tastes of the general public